ANALYSIS OF FACTORS AFFECTING WEAKNESSES OF INTERNAL CONTROL SYSTEM AT DISTRICT AND CITY GOVERNMENTS IN NORTH SUMATRA PROVINCE - Veronica, Junita Sebayang (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to analyze the effect of local government size, PAD (Local Generated Revenues), complexity, capital expenditure, total assets, and level of completion of follow-up recommendations of audit results on the weaknesses of the local government internal control system. The population was 33 districts/cities in North Sumatra Province in 5 years observation of 2011-2015. The research used saturated sampling technique and multiple linear regression analysis with the coefficient of determination, t test and F-test. The samples were 165. Secondary data were obtained from www.bpk.go.id, www.sumut.bps.go.id and BPKAD of North Sumatera Province. The results of the research showed that the local government size, PAD, capital expenditure and level of completion of follow-up recommendations of audit results had significant influence on the weakness of internal control system, while the complexity and total assets had no influence on the weakness of the internal control system. Simultaneously, local government size, PAD, complexity, capital expenditure, total assets, and level of completion of follow-up recommendations of audit results had significant influence on the weakness of the internal control system of the local government.